The effect of experiential marketing, social media marketing, and brand trust on repurchase intention in Ovo applications - Subawa, Nyoman Sri; Widhiasthini, Ni Wayan; Suastika, Ni Putu Meiliana Wulan Sari (International research journal of management, IT and social sciences, 2020)
This research was conducted to determine the effect of experiential marketing, social media marketing, and brand trust partially on repurchase intention. This research was conducted on OVO application users in Denpasar City. This study uses a quantitative approach. Respondents have taken as many as 160 respondents with a Non-probability sampling technique with the purposive sampling method. In research data obtained through the distribution of questionnaires. The testing method used in this study is the Linear Regression Test. The results in this study are experiential marketing, social media marketing, and brand trust partially positive and significant effect on repurchase intention.